Adenosine A1 receptors and mitochondria: targets of remote ischemic preconditioning - Paez, Diamela Tatiana (2019)
Adenosine is involved in classic preconditioning in most species and acts especially through adenosine A1 and A3 receptors. The aim of the present study was to evaluate whether remote ischemic preconditioning (rIPC) activates adenosine A1 receptors and improves mitochondrial function, thereby reducing myocardial infarct size. Isolated rat hearts were subjected to 30 min of global ischemia and 60 min of reperfusion [ischemia-reperfusion (I/R)]. In a second group, before isolation of the heart, a rIPC protocol (3 cycles of hindlimb I/R) was performed. Infarct size was measured with tetrazolium staining, and Akt/endothelial nitric oxide (NO) synthase (eNOS) expression/phosphorylation and mitochondrial function were evaluated after ischemia at 10 and 60 min of reperfusion. As expected, rIPC significantly decreased infarct size. This beneficial effect was abolished only when 8-cyclopentyl-1,3-dipropylxanthine (adenosine A1 receptor blocker) and NG-nitro-l-arginine methyl ester (NO synthesis inhibitor) were administered during the reperfusion phase. At the early reperfusion phase, rIPC induced significant Akt and eNOS phosphorylation, which was abolished by the perfusion with an adenosine A1 receptor blocker. I/R led to impaired mitochondrial function, which was attenuated by rIPC and mediated by adenosine A1 receptors. In conclusion, we demonstrated that rIPC limits myocardial infarct by activation of adenosine A1 receptors at early reperfusion in the isolated rat heart. Interestingly, rIPC appears to reduce myocardial infarct size by the Akt/eNOS pathway and improves mitochondrial function during myocardial reperfusion.